The Loss of Trust Due to Covid-19 Make New Southern Policy (NSP) Have to Carry Out Reforms - Kurniawati, Rhisma (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
NSP Plus is a reform carried out by South Korea to perfect the NSP. NSP Plus brings new initiatives to address the challenges faced by South Korea and NSP Plus partner countries. This study aims to describe the Covid-19 behind the reform of NSP to NSP Plus. You could say that the NSP has had a pretty good career since the NSP was founded in 2017. The question is what is the connection between Covid-19 and the reforms carried out by South Korea towards the NSP? To solve these questions using a qualitative method with a case study design on the main subject, namely NSP Plus. This research is also supported by data obtained by studying literature and the data obtained are secondary data. With research instruments from previous researchers' experiments. From this it was obtained that Covid-19 was the main factor in the NSP reform. As we know that Covid-19 has had a negative impact on various aspects of life such as health, economy, education, and technology which also has an impact on the welfare of NSP partner countries which also has an impact on trust in South Korea. As a country that is quite capable in all three matters, South Korea feels it has a responsibility to be able to restore trust and also embrace to be able to rise together through reform of the NSP with the launch of 7 new initiatives. It can be concluded that Covid-19 is an urgency for reforms in order to restore the effectiveness of South Korea's cooperation with NSP partner countries which has faded due to the waning of NSP partner countries' trust in South Korea. So that NSP Plus comes with 7 new initiatives that are certainly more effective to be able to embrace NSP partner countries to rise together from adversity due to Covid-19.